Analisis Pengelolaan Barang Milik Daerah Pada Badan Pengelolaan Keuangan Dan Pendapatan Daerah (BPKPD) Di Kabupaten Malaka - Virgilius Gracelio Seran; Petrus E. De Rosari; Cicilia A. Tungga (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This study aims to describe the management of regional property at the Regional Financial and revenue management agency (BPKPD) in Malaka Regency. The method used is qualitative with a qualitative descriptive approach involving the head of the asset sector I and the head of the security sub-sector from BPKPD Malaka Regency. This research focuses on the management of regional property at BPKPD Malaka Regency, using data collection techniques in the form of observation, interviews, and documentation which are analyzed using the Miles and Huberman model analysis technique. The results of this study indicate that the management of regional property at BPKPD Malaka Regency has been carried out properly, starting from planning needs and budgeting, procurement, use, utilization, security and maintenance, valuation, handover, deletion, destruction, administration and supervision and control guidance. In addition, the management carried out by the asset sector at BPKPD as an assistant manager is in accordance with the procedures for the regional property management cycle stipulated in Permendagri No. 19 of 2016 concerning guidelines for managing regional property, but not all have been carried out optimally, such as the delay in submitting reports at the user of goods (OPD) level, the utilization of regional property by BPKPD Malaka Regency which is only limited to the utilization of security leases carried out by BPKPD Malaka Regency does not carry out legal security.